Land-use changes triggered by the expansion of wine-growing areas: A study on the Municipalities in the Prosecco's production zone (Italy). (April 2019) - Basso, Matteo
Highlights: Prosecco is currently the most popular Italian sparkling wine in global exports. Since 2003 the production has increased by 129% in the DOCG Conegliano Valdobbiadene. In the 15 Municipalities 1063.88 ha of new vineyards were planted between 2007–2012. Out of these, 63.11% were previously cropland, 32.91% grassland and 2.55% woodland. A land-use policy aimed at harmonizing wine-growing and residential uses is needed. Abstract: The goal of this paper is to develop an analysis of the land-use changes generated by the expansion of viticulture in the Veneto Region (North-Eastern Italy). Empirical evidences were collected by the author in an area, located 50 km North of Venice, where the globally known sparkling Prosecco wine is produced. In recent years, Prosecco has become the most popular Italian sparkling wine in global exports. With a steadily expanding national and international demand, official statistics and discourses clearly shed light on Prosecco's significant productive, economic and commercial worldwide success. However, ever-growing demand implies adjusting the supply of product, which in turn means a remarkable expansion of grape-growing land. In the Prosecco region, this dynamic has become clearly evident, leading to changes in the configuration of agrarian landscapes, as well as to intense and widespread social conflicts. As the first GIS in-depth analysis of the phenomenon of Prosecco within the planning field, this paper quantitatively assesses, through institutional data, the main characteristics of a dynamic which is radically changing Veneto's landscape. Such dynamic is progressively replacing traditional cropland, grassland and woodland with vineyards producing Prosecco. The analysis focuses specifically on the 32 Municipalities – in the Province of Treviso – wholly or partly located within the two institutional Prosecco DOCG ( Denominazioni di Origine Controllate e Garantite ) zones, and calls for a renewed effective land-use policy for the region of Prosecco as a tool for harmonizing the production rationality of grape-growers and other land-uses (mostly residential).